Effect of Chlorhexidine Treatment on Microleakage of Glass Ionomer, Giomer and Methacrylate-Based Composite Restorations in Class V Cavities - Ayşe Aslı Şenol; Seda Özmen; Büşra Karabulut Gençer; Bilge Tarçın; Pınar Yılmaz Atalı (European Annals of Dental Sciences)

(untitled)
Purpose: The aim of this in vitro study was to evaluate the effect of material selection and chlorhexidine digluconate (CHX) pretreatment on microleakage in Class V cavities restored with 3 different restorative materials.Materials and Methods: Thirty freshly extracted sound human molars were cleaned and stored in distilled water. Sixty standard Class V cavities were prepared on gingival 1/3 of buccal and lingual surfaces of each tooth. Teeth were randomly assigned into 3 groups corresponding to the selected restorative material (Fuji II LC Capsule/FC, GC; Beautifil Flow Plus/BF, Shofu; and GrandioSo Flow/GF, VOCO). Lingual cavities were pre-treated with CHX (Cavity Cleanser, Bisco). The cavities were restored according to manufacturer's instructions using the materials' own adhesive systems. Teeth were stored in distilled water (24°C) for 6 months for aging. Specimens were immersed in 2% methylene blue solution for 1 h and sectioned longitudinally in buccolingual direction. Occlusal/gingival margins were examined for dye penetration and scored under x8 and x20 magnification using stereomicroscope (Leica MZ7.5, Leica Microsystems). Statistical analysis was performed using chi-square test with a significance level of p0.05). There was no statistically significant difference between the amount of microleakage of GF, FC and BF restorations in CHX-treated and untreated cavities (p>0.05).Conclusion: Application of CHX as cavity cleaner could not prevent dye penetration in Class V cavities restored with giomer, glass ionomer, and resin composites.Key Words: Chlorhexidine gluconate, composite resin, glass ionomer, microleakage.